2020
DOI: 10.3390/cells9051212
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases as Potential Biomarkers and Therapeutic Targets in Liver Diseases

Abstract: Chronic liver diseases, characterized by an excessive accumulation of extracellular matrix (ECM) resulting in scar tissue formation, are a growing health problem causing increasing morbidity and mortality worldwide. Currently, therapeutic options for tissue fibrosis are severely limited, and organ transplantation is the only treatment for the end-stage liver diseases. During liver damage, injured hepatocytes release proinflammatory factors resulting in the recruitment and activation of immune cells that activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 127 publications
2
114
0
13
Order By: Relevance
“…Extensive evidence supports a role for non-parenchymal cells, cholangiocytes, sinusoidal endothelial cell (SECs), hepatic stellate cells (HSCs), Kupffer cells (KCs) and other immune cells, including lymphocytes, in the production of MMPs and their specific inhibitors TIMPs [ 46 ]. Several studies have shown that MMP2, one of the most studied enzymes in liver fibrosis, is mainly secreted by KCs and by HSCs while MMP-9 (gelatinase B) is predominantly expressed in KCs but can be also expressed by neutrophils, macrophages and fibroblasts [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive evidence supports a role for non-parenchymal cells, cholangiocytes, sinusoidal endothelial cell (SECs), hepatic stellate cells (HSCs), Kupffer cells (KCs) and other immune cells, including lymphocytes, in the production of MMPs and their specific inhibitors TIMPs [ 46 ]. Several studies have shown that MMP2, one of the most studied enzymes in liver fibrosis, is mainly secreted by KCs and by HSCs while MMP-9 (gelatinase B) is predominantly expressed in KCs but can be also expressed by neutrophils, macrophages and fibroblasts [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis occurs when healthy liver tissues becomes scarred from chronic liver injury and inflammatory responses, and therefore cannot function normally [ 19 , 20 ]. Chronic liver damage leads to liver fibrosis in conjunction with the accumulation of ECM proteins, which is a typical characteristic of most chronic liver diseases [ 21 ]. Activated HSCs are major ECM-producing cells in an injured liver; these cells are activated by fibrogenic mediators, such as TGF-β [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-Time RT-PCR It was performed as previously described, 28) and the primers used were as follows: α-smooth muscle actin (α-SMA), 5′-ACT GGG ACG ACA TGG AAA AG-3′ and 5′-TAG ATG GGG ACA TTG TGG GT-3′; PDGF-Rβ, 5′-ATG CCT TAC CAC ATC CGC TC-3′ and 5′-ACA TTG CAG GTG TAG GTC CCC-3′; PDGF-B, 5′-AGG AGA CCC TTG GAG CCT AG-3′ and 5′-CAT CGA GAC AGA CGG ACG AG-3′; collagen type I alpha 2 (COL1A2), 5′-ACC TGG TCA AAC TGG TCC TG-3′ and 5′-GTG TCC CCT AAT GCC TTT GA-3′; and β-actin, 5′-TCC ACC TCC AGC AGA TGT GG-3′ and 5′-GCA TTT GCG GTG GAC GAT-3′.…”
Section: Methodsmentioning
confidence: 99%